2013
DOI: 10.1103/physrevb.87.224203
|View full text |Cite
|
Sign up to set email alerts
|

Helical glasses near ferromagnetic quantum criticality

Abstract: We study the effects of quenched charge disorder on the phase reconstruction near itinerant ferromagnetic quantum critical points in three spatial dimensions. Combining a Replica-disorder average with a fermionic version of the quantum order-by-disorder mechanism, we show that weak disorder destabilizes the ferromagnetic state and enhances the susceptibility towards incommensurate, spiral magnetic ordering. The Goldstone modes of the spiral phase are governed by a 3d-XY model. The induced disorder in the pitch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Recently it has been shown theoretically that another new phase possibly stabilizes near the FM-PM QPT [51][52][53][54][55][56] ; if there are quantum fluctuations in terms of fermionic particle-hole excitations on the Fermi surface, some deformations of the Fermi surface enhance the phase space available for the quantum fluctuations, and such a Fermi-surface instability causes another type of ordering to gain the free energy of the system [53][54][55][56] . It has been shown that two cases of new ordering are possible near the FM-PM QPT: (i) spiral magnetic phase, and (ii) spin-nematic phase 54 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently it has been shown theoretically that another new phase possibly stabilizes near the FM-PM QPT [51][52][53][54][55][56] ; if there are quantum fluctuations in terms of fermionic particle-hole excitations on the Fermi surface, some deformations of the Fermi surface enhance the phase space available for the quantum fluctuations, and such a Fermi-surface instability causes another type of ordering to gain the free energy of the system [53][54][55][56] . It has been shown that two cases of new ordering are possible near the FM-PM QPT: (i) spiral magnetic phase, and (ii) spin-nematic phase 54 .…”
Section: Resultsmentioning
confidence: 99%
“…LaCrGe 3 is therefore an example of a simple 3d-electrons ferromagnetic system for which a new magnetic phase appears as the Curie temperature is suppressed by pressure. Interestingly, this scenario has been considered recently by several theories [15,[23][24][25][26][27][28][29]. The idea is that particle-hole excitations corresponding to long wavelength correlations lead either to a change of order of the transition to the first order or to a new magnetic phase.…”
Section: Quantum Wingmentioning
confidence: 99%
“…Indeed, it was noted in Ref. [66] that the fluctuation-induced helimagnet might be rather susceptible to the effects of disorder, possibly explaining the apparent spin glass behaviour in the region of the phase diagram of CeFePO(Ref. [67]) where helimagnetism might otherwise be predicted.…”
Section: Partial Order In Mnsimentioning
confidence: 99%